Synthesis of Double-Shell Hollow TiO2@ZIF-8 Nanoparticles With Enhanced Photocatalytic Activities - Fu, Ning; Ren, Xue-chang (Frontiers in Chemistry, 2020)
Synthesis of semiconductor-MOFs heterostructure photocatalysts have attracted considerable attention for their thermal stability, controllable crystallinity and enhanced photocatalytic activity. In this work, the hollow nanostructure of anatase TiO2 was prepared by etching SiO2 from core-shell SiO2@TiO2 nanoparticles. ZIF-8, one of the metal-organic frameworks (MOFs) was hybrid synthesized on the surface of hollow TiO2 and formed double-shell hollow nanoparticles. The photocatalytic activity of the double-shell hollow TiO2@ZIF-8 nanoparticles towards methylene blue (MB) under UV light irradiation was processed and the highest photocatalytic efficiency of 99.1% was shown compared with TiO2 and SiO2@TiO2 nanoparticles. This study suggests a promising approach to achieve advanced photocatalytic performance towards dye degradation using MOFs as surface engineering of semiconductors.